Effect of switching from cigarette smoking to the use of the tobacco heating system on periodontitis treatment outcome: Periodontal parameter results from a multicenter Japanese study - Pouly, Sandrine; Ng, Wee Teck; Blanc, Nicolas; Hession, Paul; Zanetti, Filippo; Battey, James N. D.; de La Bourdonnaye, Guillaume; Heremans, Annie; Haziza, Christelle (Frontiers in Dental Medicine, 2022)
Objectives We conducted a 6-month randomized clinical study to evaluate the impact of exposure to the aerosol of the Tobacco Heating System (THS), a smoke-free alternative to cigarettes, on changes in periodontal parameters after scaling and root planing (SRP) for periodontitis in subjects who were either continuing to smoke cigarettes or had switched to THS. Material and methods Smokers with generalized periodontitis were randomized to continue smoking cigarettes or switch to THS use. They underwent SRP for up to 8 weeks, with dental assessments conducted at baseline and at 3 and 6 months after the first treatment. Results After SRP treatment, all groups showed improvements in the mean full-mouth probing depth (PD), full-mouth clinical attachment level (CAL), gingival inflammation score, plaque control record (PCR), and bleeding on probing (BoP). There were no statistically significant intergroup differences. However, as compared to smokers, THS users showed a trend toward more favorable outcomes in BoP, PCR, and PD improvement at sites with higher initial PD (≥7 mm). Conclusions Our results indicate that SRP improves the course of periodontitis similarly in cigarette smokers and THS users. The beneficial effects of this treatment might mask the favorable changes that may occur upon modifying one of the several periodontitis risk factors, such as cigarette smoking. Clinical trial registration ClinicalTrials.gov, identifer: NCT03364751.